Influence of feeding frequency on performance and nitrogen metabolism in gestating swine - Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The influence of feeding frequency on performance and nitrogen metabolism in gestating swine was studied by feeding 4 pounds daily, 8 pounds every other day, or 12 pounds every third day. All animals were maintained in dry lots with portable housing and were fed a 12%-protein, corn-soybean meal diet in individual feeding stalls. Three successive 6 day collection studies were conducted with 6 gilts. Nitrogen digestibility was not influenced by feeding frequency. However, nitrogen retention decreased as intervals between feeding increased. Gilts fed 4 pounds daily retained more nitrogen than those fed 8 pounds every other day, while those fed 8 pounds every other day retained more than those fed 12 pounds every third day. Although nitrogen retention was significantly influenced by feeding frequency, sow performance as measured by number of pigs born, birth weight, number of pigs weaned, and weight of pigs at 28 days was not.
Swine Industry Day 1973 is known as Swine Day, 1973
Keywords: Swine; Feeding frequency; Performance; Nitrogen metabolism; Gestation